The Realistic Joneses. - Eno, Will (OBERON Books Ltd, 2014)
Meet Bob and Jennifer and their new neighbours, John and Pony, two suburban couples who have even more in common thantheir identical homes and their shared last names. As their relationships begin to irrevocably intertwine, the Joneses must decidebetween their idyllic fantasies and their imperfect realities. This contemporary comedy explores how our joys and sorrows - and how we choose to face them - can come to define our lives.